Effect of Inversion Asymmetry on Quantum Confinement of Dirac Semimetal Cd3As2. Issue 1 (February 2021) - Chou, Christopher; Goyal, Manik
Abstract: The discovery of the 3D Topological Dirac semimetal Cd3 As2 presents a new class of semimetals because of its unique electronic structure and transport properties, demonstrating potential in novel topological devices. Promising properties of Cd3 As2 include its topological surface states, ultrahigh electron mobility, and linear band dispersion. We evaluated the effect of inversion asymmetry on quantum confinement of Cd3 As2 by measuring its electronic properties with and without hybridization through the quantum transport simulation package Kwant. Due to confinement, Cd3 As2 exhibits a similar state to a 3D topological insulator because the transport in the bulk state becomes gapped, causing the surface state to dominate transport similar to 3D topological insulators. Thus, we can compare transport properties and band structure of Cd3 As2 with other known 3D topological insulators such as HgTe and (Bi1- x Sb x )2 Te3 through the analysis of previous electrostatic gating studies. We observe the lifting of the spin degeneracy due to inversion asymmetry and demonstrate that Cd3 As2 provides a promising platform for topological device applications.